RISK CONTROL PROGRAM FOR THE ELECTRICITY EXHIBITION IN A BANK - Lopez R., Juan (2002)
In the present study a Risk Control Program for exposures to electric power in a bank is approached, showing the main guidelines contributing to diminish electric accidents in a bank, and thus lessen short-circuits consequences, such as fires and losses of information.